Perceptions and Beliefs about Cervical Cancer and Screening Services: A Qualitative Analysis among Female Sex Workers in Abuja, Nigeria - Ruth, Kehinde Dayo; Ekama, Ilesanmi Rose; Ojo, Aluko Joel (NIU Journal of Social Sciences, 2019)
Purpose : Cervical screening allows for early detection of changes in the cervix which may suggest    cervical cancer, and therefore creates opportunity for initiation of prevention modalities in good time.   Literature confirms that perceptions of individuals about any services influence the utilization of such services.  FSW are high risk group for cervical cancer, yet their perceptions about cervical cancer screening has not been fully explored in Nigeria. This study is therefore a report of a qualitative analysis of the perceptions of FSW about cervical cancer screening services Methods : The study utilized a qualitative design to elicit the perceptions of FSW on cervical cancer screening. A Focused group discussion (FGD) was conducted among 18 purposively selected FSWs in selected brothels in Bwari Council. Discussions were centered on perception of cervical cancer, screening services, preventive practices, and actions taken when   positive results are received. Data were analyzed using Atlas t.i software package. Results: Respondents were aware of cervical cancer screening, however knowledge about cervical cancer was poor. Majority understood that they were at risk for cervical cancer although they could not understand abnormal results. Also, majority understand the preventable risk between cervical cancer screening and cervical cancer. Conclusions: Findings suggest a poor perception about cervical cancer cancer and screening services.  This is an indication for educational intervention to be designed purposively for the FSWs in order to reduce the burden of cervical cancer in Nigeria and sub-Saharan Africa. Keywords: Female Sex Workers, cervical cancer screening, perception